Um julgamento de concretude de palavras - Calais, Lucila Leal [UNIFESP] (2012)
PURPOSE: To describe the judgement of the concreteness of a set of 162 Brazilian Portuguese words, prior to the elaboration of a speech recognition test, as well as to verify the influence of variables such as the frequency of occurrence of the words and age and undergraduate program year of the participants on the concreteness ratings. METHODS: Fifty undergraduate Speech-Language Pathology and Audiology students from a public university rated the concreteness of a set of 162 words using a seven-point scale where the lowest concreteness degree was represented by number one and the highest by number seven. Participants were free to choose any number in the scale. RESULTS: The results showed a tri-modal distribution of values, suggesting the classification of three categories, according to the concreteness rating. The low concreteness category ranged from 1.76 to 3.45; the medium concreteness category, from 3.46 to 4.95; and the high concreteness rating, from 4.96 to 6.70. Positive correlation was found between the concreteness rating and the coefficient of variation, whereby the higher the rating attributed to a word, the lesser variation in the responses. No significant correlation was found between concreteness ratings and the frequency of occurrence of words. The influence of age and undergraduate year was significant for some correlations. CONCLUSION: Results showed three concreteness categories, and suggest that concreteness can be considered an independent attribute of words, since their frequency of occurrence, as well as participants' age and undergraduate program year did not influence the ratings attributed. The words classified in the high concreteness category were subsequently used for the elaboration of a speech recognition test.